Portrait des minorités de langue officielle au Canada : les francophones de l’Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistique Canada Division de la statistique sociale et autochtone, 2010)

Enjeux du vieillissement chez les Africains en milieu francophone minoritaire canadien - Mulatris, Paulin; Bahi, Boniface (Alterstice, 2014)
Les enjeux du vieillissement des populations francophones d’origine africaine subsaharienne sont très peu connus. Une analyse de données qualitatives portant sur le vécu socioculturel et les déterminants de la santé, obtenues au moyen d’entrevues semi-structurées auprès d’immigrants francophones africains subsahariens des régions urbaines d’Edmonton et Calgary, permet de constater que cette population cumule des défis culturels et économiques qui les poussent à développer un mode de vie inapproprié aux conditions d’un vieillissement en santé. La nécessité que ces Néo-Canadiens développent des habitudes de vie adaptées mène à une réflexion sur les conditions socioéconomiques auxquelles ils font face et sur l’adaptation culturelle des soins.

Francophones living with HIV/AIDS in Ontario: The unknown reality of an invisible cultural minority - Samson, Andre. A.; Spector Noah. M. P. (AIDS Care, 2012)
A strong body of evidence demonstrates that education, prevention and intervention, in the context of HIV/AIDS, should take ethno-racial diversity into account. The current research focuses on the cultural sensitivity manifested by AIDS service organisation ASO professionals towards Francophone minority persons living with HIV/AIDS Francophone PHAs in the two main urban centres of Ontario: Ottawa and Toronto. More specifically, this qualitative research will describe two different points of view: Francophone PHA service users n17 and ASO professionals n12. Data were collected from multiple focus groups and analysed using a phenomenological methodology. The analysis revealed that an important difference exists in the perceptions of language as an integral part of ethno-racial diversity. For ASO professionals, language is perceived as a simple tool of communication. For Francophones living with HIV/AIDS, however, language is perceived as a way to convey sensitivity to their cultural reality and a full recognition of their Canadian citizenship. This research showed that cultural sensitivity should include a linguistic aspect when it comes to health-related services, especially in the context of an officially bilingual country.